2016
DOI: 10.1007/s10886-016-0788-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and behavioral responses of female African rice gall midge, Orseolia oryzivora Harris and Gagné, to host plant volatiles

Abstract: African rice gall midge, Orseolia oryzivora Harris and Gagné, is a major pest of rice in Africa. Depsite its economic importance, its chemical ecology is not well understood. Here, we assessed behavioral and electrophysiological responses of O. oryzivora to host plant volatiles. In olfactometer bioassays, mated female O. oryzivora were attracted to volatiles emitted from intact rice plants but were repelled by volatiles collected from plants infested by conspecifics. In a choice test, there was a preference fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Homoterpenes (monoterpenes with an added methylene group) have also been studied as allelochemicals . These terpenoids can arise via different biosynthetic routes in a tissue‐specific manner; in the case of 4,8‐dimethyl‐1,3,7‐nonatriene, it is synthesized by degradation of the C30 triterpene diol, arabidiol, and catalyzed by the Brassicaceae‐specific cytochrome P450 monooxygenase CYP705A1 …”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Homoterpenes (monoterpenes with an added methylene group) have also been studied as allelochemicals . These terpenoids can arise via different biosynthetic routes in a tissue‐specific manner; in the case of 4,8‐dimethyl‐1,3,7‐nonatriene, it is synthesized by degradation of the C30 triterpene diol, arabidiol, and catalyzed by the Brassicaceae‐specific cytochrome P450 monooxygenase CYP705A1 …”
Section: Chemistrymentioning
confidence: 99%
“…81 Homoterpenes (monoterpenes with an added methylene group) have also been studied as allelochemicals. 82 These terpenoids can arise via different biosynthetic routes in a tissue-specific manner; in the case of 4,8-dimethyl-1,3,7-nonatriene, it is synthesized by degradation of the C30 triterpene diol, arabidiol, and catalyzed by the Brassicaceae-specific cytochrome P450 monooxygenase CYP705A1. 83,84 Allelopathy studies can be used to discover new monoterpenes, such as (−)-(1R*,2S*,4R*,5S*)-3,3-dimethyl-5-hydroxybicyclo[2,2,1] hept-2-ylmethanol isolated from Eupatorium adenophorum, which inhibited Arabidopsis thaliana seed germination by 20%.…”
Section: Monoterpenesmentioning
confidence: 99%
“…It was found that less damage was caused by Paropsisterna tigrina adults in Melalecua alternifolia , in the presence of a high concentration of terpinolene [ 59 ]. In addition, volatiles containing the same terpenoids present in intact and infested rice plants attract or repel the rice pest Orseolia oryzivora depending on their concentrations [ 60 ] Table 2 summarizes examples from relevant studies.…”
Section: Terpenoids In Plant–insect Interactionsmentioning
confidence: 99%
“…Female orange wheat blossom cecidomyiid midges Sitodiplosis mosellana were attracted by key compounds, e.g., ( Z )-3-hexenyl acetate, acetophenone, and 3-carene, present in minor proportions in the overall volatile profile of wheat panicles ( Birkett et al, 2004 ). The African rice gall cecidomyiid midge Orseolia oryzivora preferred volatiles from uninfested plants while those from infested plants served as repellents; the major difference between these volatile profiles was a considerable increase in the HIPV ( E )-β-caryophyllene ( Ogah et al, 2017 ).…”
Section: Plant Volatile Organic Compounds (Vocs) That Attract Gallersmentioning
confidence: 99%